Oxidative Hydrophenylation of Ethylene Using a Cationic Ru(II) Catalyst: Styrene Production with Ethylene as the Oxidant. Issue 10 (8th November 2017) - Jia, Xiaofan; Gary, J. Brannon; Gu, Shaojin; Cundari, Thomas R.; Gunnoe, T. Brent
Abstract: The complex [(MeOTTM)Ru(P(OCH2 )3 CEt)(NCMe)Ph][BAr′4 ] (MeOTMM=4, 4', 4''‐(methoxymethanetriyl)‐tris(1‐benzyl‐1H‐1, 2, 3‐triazole), BAr′4 =tetrakis[3, 5‐bis(trifluoromethyl)phenyl]borate) is used to catalyze the hydrophenylation of ethylene to produce styrene and ethylbenzene. The selectivity of styrene versus ethylbenzene varies as a function of ethylene pressure, and replacing the MeOTTM ligand with tris(1‐phenyl‐1H‐1, 2, 3‐triazol‐4‐yl)methanol reduces the selectivity toward styrene. For styrene production ethylene serves as the oxidant to produce ethane, as determined by both 1 H NMR spectroscopy and GC‐MS. The Ru(III/II) potentials of [(MeOTTM)Ru[P(OCH2 )3 CEt](NCMe)Ph][BAr′4 ] (0.86 V) and [(HC(pz 5 )3 )Ru[P(OCH2 )3 CEt](NCMe)Ph][BAr′4 ] (0.82 V) (HC(pz 5 )3 =tris(5‐methyl‐pyrazolyl)methane) are nearly identical. Since catalytic conversion of ethylene and benzene by [(HC(pz 5 )3 )Ru[P(OCH2 )3 CEt](NCMe)Ph][BAr′4 ] is known to selectively produce ethylbenzene, the formation of styrene using [(MeOTTM)Ru[P(OCH2 )3 CEt](NCMe)Ph][BAr′4 ] is attributed to the substituents on the triazole rings of the MeOTTM ligand. Abstract :